Investigasi Adhesi Fisik, Nilai CBR Dan Ketahanan Deformasi Bahan RAP - KHOLIQ, Muhammad Abdul (2016)
The highway is a public infrastructure that is often used in performing daily activities, because of the importance of the role of the good road conditions will greatly affect the smoothness and comfort of road users. The problems of road damage that occurs every year push to make improvements, the use of recycled asphalt or RAP (Reclaymet asphalt pavement) one of the solutions to overcome the problems of the road. The aim of research utilizing the waste pavement and modified in order to improve the quality of RAP mixture to be used again.              Research using laboratory tests on the physical adhesion properties, the value of CBR and RAP material deformation resistance and fresh aggregate. In the study carried out preparation, preparation tools and materials. This experiment is testing abrasion, density, gradation analysis, density analysis, test Dynamic Static immersion test and immersion test to determine the adhesion of asphalt to the material. Examination of the value of CBR and deformation resistance using a CBR (California Bearing Ratio) and appliance UTM (Universal Testing Machine). Overall in this study made 24 test specimens to investigate the physical properties of adhesion, the value of CBR and deformation resistance. In a study investigating the physical adhesion properties, the value of CBR and deformation resistance, shows that, overall physical adhesion value of RAP and fresh aggregate belt has the power quality of the material either, although both in specs but fresh aggregate value better than RAP material. CBR value and deformation resistance indicates the quality of the fresh aggregate material is higher than the RAP material. Results of testing the static immersion test RAP average gained 98.48, while for the fresh aggregate average gained 99.87. RAP dynamic testing immersion test average of 97.36 was obtained for a fresh aggregate obtained 99.54. RAP test results obtained maximum density of 1.64 g / cm3, the optimum water content of 5.1% to the value of CBR 32.06, the value of UTM = 33.50. The fresh aggregate density, maximum density of 1.74 g / cm3, the optimum water content of 5.6%, the value of CBR = 78.50 and the value of UTM = 59.96. RAP deformation test results using a CBR = 0.10 inches (650lb), fresh aggregate = 0.06 inches (1700lb). RAP deformation testing using a UTM = 0.27 inches (1200lb), fresh aggregate = 0.12 inches (940lb). The final conclusion is that the RAP and fresh aggregate material has good adhesion values ​​but RAP material to the value of the carrying capacity and deformation have low quality.